2018
DOI: 10.1002/jper.18-0471
|View full text |Cite
|
Sign up to set email alerts
|

Significance of keratinized mucosa/gingiva on peri‐implant and adjacent periodontal conditions in erratic maintenance compliers

Abstract: Background Given the fact that most patients are not regular compliers in supportive peri‐implant maintenance programs, it is of interest to examine the significance of the peri‐implant soft tissue characteristics in relationship to the onset of peri‐implant diseases. Methods Based on an a priori statistical power calculation, a cross‐sectional study was conducted on erratic peri‐implant maintenance compliers (<2 times/year) to examine the significance of keratinized mucosa (KM) and gingival tissue (KT) on per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
202
4
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(223 citation statements)
references
References 49 publications
12
202
4
5
Order By: Relevance
“…Current evidence underlines the importance of frequent periodontal and peri‐implant maintenance, suggesting that in highly compliant patients, KM plays a null role in the prevention of biological complications (Lim et al, ). Conversely, in poorly compliant patients, the presence of ≥2 mm of KM has been demonstrated to be beneficial for long‐term outcomes (Monje & Blasi, ; Romanos, Grizas, & Nentwig, ). Generally, the influence of peri‐implant KM on peri‐implantitis therapeutic outcomes is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence underlines the importance of frequent periodontal and peri‐implant maintenance, suggesting that in highly compliant patients, KM plays a null role in the prevention of biological complications (Lim et al, ). Conversely, in poorly compliant patients, the presence of ≥2 mm of KM has been demonstrated to be beneficial for long‐term outcomes (Monje & Blasi, ; Romanos, Grizas, & Nentwig, ). Generally, the influence of peri‐implant KM on peri‐implantitis therapeutic outcomes is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…That study compared the shift of MGJ between the groups with/without primary flap closure, demonstrating 3.83 ± 2.68 and 1.21 ± 0.94 mm of shift, respectively. Despite controversy regarding keratinized mucosa around implants (Lim, Wiedemeier, Hammerle, & Thoma, ; Monje & Blasi, ; Schwarz, Derks, Monje, & Wang, ), a recent systematic review favoured the soft tissue grafting procedure for gaining keratinized mucosa in order to establish peri‐implant health (Thoma et al, ). Less change in the MGJ following ARP with the open‐healing approach may contribute to the stable mucosal situation around the implants without an additional soft tissue grafting procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was further exhibited that~25% displayed a circumferential defect combined with a buccal dehiscence-type defect. [26][27][28] However, breaking down this data, it was found that, in the mandibular anterior peri-implantitis implants, 67.7% lacked KM, while periimplantitis in the maxillary anterior and posterior sites occurred 75% and 46.2%, in areas ≥2 mm KM, respectively. Nevertheless, the rate of peri-implantitis defects displaying in a 2-3-walls infraosseous morphology was slightly greater than the aforementioned studies.…”
Section: Agreements and Disagreements With Previous Studiesmentioning
confidence: 99%